Synchronous Gastrointestinal Stromal Tumor (GIST) with pancreatic adenocarcinoma: A case report - Terukumar Chandrasekaran; Nik Amin Sahid Nik Lah; Thanesh Kumar Maiyauen (Elsevier, 2022)
Introduction: Gastrointestinal Stromal Tumors (GIST) are rare mesenchymal neoplasm of gastrointestinal tract. Stomach is the most common site affected by GIST compared to other places in gastrointestinal track. The coexistence of GIST with another malignancy represents a rare phenomenon with few literature reported. Case presentation: We present here 65 years old patient with stomach GIST and synchronous pancreatic adenocarcionoma discovered during surgery for suspected pancreatic mucinious cystadenoma. Distal pancreaticosplenectomy with excision of GIST Tumor & wedge resection of stomach was done. Histopathological examination of resected specimens reported the margins are clear. Discussion: In this article we discuss on the option of systemic therapy versus upfront surgery and their outcome benefit based on literature review. Conclusion: The coexistence of GIST with pancreatic adenocarcinoma is a rare condition. High clinical analysis needed during laparotomy for GIST to detect a synchronous tumor. In a case of GIST the surgeon should recognize the possibility of another tumor with different histological origin. Surgical excision is the mainstay of therapy and it has proven to be curative for our patient. . Due to its rare occurrence and limited literature further studies has to be done on GIST with other synchronous tumor to help the surgeon to manage the patient optimally.